2022
DOI: 10.1136/svn-2021-001476
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial microvesicles and their carried miR-125a-5p: potential biomarkers for ischaemic stroke

Abstract: BackgroundEndothelial microvesicles (EMVs) are closely associated with the status of endothelial cells (ECs). Our earlier study has shown that EMVs could exert protective roles in ECs by transferring their carried miR-125a-5p. However, whether circulating EMVs and their carried miR-125a-5p can be used as biomarkers in ischaemic stroke (IS) are remain unknown. Methods We recruited 72 subjects with IS, 60 subjects with high stroke risk and 56 age-matched controls. The circulating EMVs and their carried miR-125a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Forest plot for the correlation between the concentration of miR-125a-5p, miR-125b-5p, miR-126, miR-185, miR-195, miR-335, and NIHSS score; in certain cases, we address separately all reported studies (A) and (B) only studies with reported same miRNA source. References: miR-125a-5p: [40,43]; miR-125b-5p: [43,44,61,62]; miR-126: [64,65]; miR-185: [64,65,87]; miR-195: [51,66,67]; miR-335: [76,78].…”
Section: Discussionmentioning
confidence: 99%
“…Forest plot for the correlation between the concentration of miR-125a-5p, miR-125b-5p, miR-126, miR-185, miR-195, miR-335, and NIHSS score; in certain cases, we address separately all reported studies (A) and (B) only studies with reported same miRNA source. References: miR-125a-5p: [40,43]; miR-125b-5p: [43,44,61,62]; miR-126: [64,65]; miR-185: [64,65,87]; miR-195: [51,66,67]; miR-335: [76,78].…”
Section: Discussionmentioning
confidence: 99%